Tomoregulin-1 prevents cardiac hypertrophy after pressure overload in mice by inhibiting TAK1-JNK pathways - Dan Bao; Dan Lu; Ning Liu; Wei Dong; Ying-Dong Lu; Chuan Qin; Lian-Feng Zhang (The Company of Biologists, 2015)
Cardiac hypertrophy is associated with many forms of heart disease, and identifying important modifier genes involved in the pathogenesis of cardiac hypertrophy could lead to the development of new therapeutic strategies. Tomoregulin-1 is a growth factor that is primarily involved in embryonic development and adult central nervous system (CNS) function, and it is expressed abnormally in a variety of CNS pathologies. Tomoregulin-1 is also expressed in the myocardium. However, the effects of tomoregulin-1 on the heart, particularly on cardiac hypertrophy, remains unknown. The aim of the study is to examine whether and by what mechanism tomoregulin-1 regulates the development of cardiac hypertrophy induced by pressure overload. In this study, we found that tomoregulin-1 was significantly upregulated in two cardiac hypertrophy models: cTnTR92Q transgenic mice and thoracic aorta constriction (TAC)-induced cardiac hypertrophy mice. The transgenic overexpression of tomoregulin-1 increased the survival rate, improved the cardiac geometry and functional parameters of echocardiography, and decreased the degree of cardiac hypertrophy of the TAC mice, whereas knockdown of tomoregulin-1 expression resulted in an opposite phenotype and exacerbated phenotypes of cardiac hypertrophy induced by TAC. A possible mechanism by which tomoregulin-1 regulates the development of cardiac hypertrophy in TAC-induced cardiac hypertrophy is through inhibiting TGFβ non-canonical (TAK1-JNK) pathways in the myocardium. Tomoregulin-1 plays a protective role in the modulation of adverse cardiac remodeling from pressure overload in mice. Tomoregulin-1 could be a therapeutic target to control the development of cardiac hypertrophy.